Design and construction of hierarchical and cross-regional SDN verification and demonstration system - Zhifeng LIU; Xia YIN; Zhiliang WANG; Xingang SHI; Yiqiang HUA; Xiaohong HUANG; Liang WEI; Jiangyuan YAO; Han ZHANG; Man ZENG; Zijun SU; Shuai LIU (Dianxin kexue)
SDN architecture could bring excellent flexibility and manageability to the network.In order to provide a large-scale verification testbed and a pilot deployment environment for SDN-based new technologies and applications,a hierarchical and cross-regional SDN verification and demonstration system over CERNET was proposed,and a SDN verification and demonstration core network consisted of nine cities and thirteen nodes and an access network containing three data centers was built.Based on this system,several SDN-based technologies and applications such as CPE virtualization line service,IPv4/IPv6 transition technology,traffic monitoring and scheduling application and data center applications were deployed,verified and demonstrated.